Cultural representations of feminicidio at the US-Mexico border - Finnegan, Nuala (Global gender, 2019)
Acknowledgements -- Introduction: no nos cabe tanta muerte [unbearable deaths] -- Framing feminicidio : the spectral politics of death in Ciudad Juárez -- Sacrificial screams : excess in Àlex Rigola's stage adaptation of 2666 -- Remember them : ethics and witnessing in artistic responses to feminicide -- Resilience and renewal in documentary film about feminicidio in Ciudad Juárez -- Toward an activist poetics in fiction about feminicidio in Ciudad Juárez -- Conclusion: notes towards the possible -- Appendix -- Index